Mitral valve surgery after failed transcatheter edge-to-edge repairCentral MessagePerspective - Piotr Mazur, MD, PhD; Arman Arghami, MD, MPH; Clark Zheng; Mohamad Alkhouli, MD; Hartzell V. Schaff, MD; Joseph Dearani, MD; Richard C. Daly, MD; Kevin Greason, MD; Juan A. Crestanello, MD (JTCVS Techniques)
Objective: Mitral valve operations for failed transcatheter edge-to-edge repair (TEER) are increasing. This study investigated the indications, surgical procedures, and outcomes after surgery for failed TEER. Methods: We analyzed records of patients who underwent mitral valve operations after TEER between January 2013 and September 2021. Patient characteristics, clip number and location, indications, timing, surgery type, and outcomes were evaluated. Results: A total of 41 patients (median age, 77 years; 14 women; median Society of Thoracic Surgeons predicted risk of mortality score, 9.4% [5.6%-12.6%]; and previous cardiac surgery in 21 patients) underwent mitral valve surgery at a median of 8 months (range, 4-16 months) after TEER. One clip was implanted in 24 patients and 2 or more in 17 patients. Indications for surgery were severe mitral regurgitation in 33, severe mitral stenosis in 1 patient, and both in 7 patients. Operations were performed via sternotomy in 37 patients and lateral thoracotomy in 4 patients. The mitral valve was replaced in all patients (bioprosthesis in 35 patients and a mechanical valve in 6 patients). Concomitant procedures were performed in 30 patients. Operative mortality was 5% (observed to expected ratio, 0.53) and did not differ for primary procedures versus reoperations. Echocardiographic follow-up demonstrated no or trivial mitral regurgitation in 34 patients, mild mitral regurgitation in 5 patients, and moderate perivalvular mitral regurgitation in 1 patient with severe mitral annular calcification. At a median follow-up of 1.5 years (interquartile range, 4.7 months-2.7 years), the actuarial survival was 79%. Conclusions: Mitral valve replacement can be performed safely after failed TEER with operative mortality lower than expected even in high-risk patients. Video Abstract: